2008
DOI: 10.2174/1874306400802010016
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Ventilation Applied for Recovery from Exercise-Induced Diaphragmatic Fatigue

Abstract: Abstract:Background: Exercise-induced diaphragmatic fatigue (DF) is conventionally considered to reflect impaired diaphragm function resulting from load imposed on the diaphragm during exercise and is known to be reduced by the application of non-invasive ventilation (NIV) during heavy-intensity exercise testing (HEET). On that physiological condition NIV applied for diaphragm unloading during recovery from exercise should be capable of accelerating recovery from DF and therewith prolonging exercise time to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…One possible reason we did not find RMF is the rest intervals in the HIT protocols allowed for the respiratory muscles to recover and delay the onset of fatigue. This is not likely and only supported by 1 study, to our knowledge, that showed that respiratory muscles can recover from fatigue in 1.5 minutes postexercise (22). The majority of research studies show a reduction in maximal mouth pressures beyond 10 minutes after exercise until exhaustion in moderately active subjects (26).…”
Section: Discussionmentioning
confidence: 87%
“…One possible reason we did not find RMF is the rest intervals in the HIT protocols allowed for the respiratory muscles to recover and delay the onset of fatigue. This is not likely and only supported by 1 study, to our knowledge, that showed that respiratory muscles can recover from fatigue in 1.5 minutes postexercise (22). The majority of research studies show a reduction in maximal mouth pressures beyond 10 minutes after exercise until exhaustion in moderately active subjects (26).…”
Section: Discussionmentioning
confidence: 87%
“…Although volitional measures of fatigue may be confounded by the presence of central fatigue, the decrease in end-inspiratory V rc,p with no change in the other two compartments is considered an independent indicator of inspiratory rib cage muscle fatigue. Furthermore, the few studies assessing respiratory muscle fatigue after exercise with both measurement of oesophageal and gastric pressure during nerve stimulation and during voluntary respiratory manoeuvres show a decrease in twitch pressures with smaller decreases (or no significant change) in pressures during voluntary manoeuvres (Johnson et al, 1993;Mador et al, 1993;Taylor et al, 2006;Kabitz et al, 2008;Taylor and Romer 2008).…”
Section: Limitationsmentioning
confidence: 99%